Assessment of ecotoxicity of the bismuth by biological indicators of soil condition - Lyudmila Sudina; Sergey Kolesnikov; Tatiana Minnikova; Kamil Kazeev; Svetlana Sushkova; Tatiana Minkina (Eurasian Journal of Soil Science, 2021)
The present study was performed for the ecotoxicity assessment of the bismuth (Bi) effect on the biological indicators of soil condition: total number of soil bacteria, catalase activity, dehydrogenases activity and germination of Radish seeds and length of the Radish roots. Three soil types with significantly different resistance ability to heavy metal pollution were studied: Haplic Chernozems Calcic, Haplic Arenosols Eutric and Haplic Cambisols Eutric.Soil contamination of Bi was simulated in the lab (3, 30 and 300 mg kg-1 dry weight). Changes in the biological parameters of the soil were assessed at 10 day treatment. The data obtained showed that the soils contaminated with Bi in South Russia generally characterized by oppression of the biological properties. The total number of bacteria and enzymatic activity (catalase and dehydrogenases) decreased over the Bi contamination. The indicators of phytotoxicity (germination of radish seeds) increase when bismuth 3 and 30 mg kg-1 is added to the soil. The degree of deterioration in biological properties depends on the concentration of Bi in the soil and the period of time after the onset of pollution. Resistance of soil types to Bi pollution can be described by the following decreasing series: Haplic Chernozem Calcic > Haplic Arenosols Eutric > Haplic Cambisols Eutric. The following regional maximum permissible concentrations (rMPC) of Bi have been proposed: Haplic Chernozem Calcic – 8.5 mg kg-1, Haplic Arenosols Eutric – 2.2 mg kg-1 and Haplic Cambisols Eutric – 1.8 mg kg-1.